Activation of the Innate Signaling Molecule MAVS by Bunyavirus Infection Upregulates the Adaptor Protein SARM1, Leading to Neuronal Death - Mukherjee, Piyali (Immunity, 2013)
La Crosse virus (LACV), a zoonotic Bunyavirus, is a major cause of pediatric viral encephalitis in the United States. A hallmark of neurological diseases caused by LACV and other encephalitic viruses is the induction of neuronal cell death. Innate immune responses have been implicated in neuronal damage, but no mechanism has been elucidated. By using in vitro studies in primary neurons and in vivo studies in mice, we have shown that LACV infection induced the RNA helicase, RIG-I, and mitochondrial antiviral signaling protein (MAVS) signaling pathway, resulting in upregulation of the sterile alpha and TIR-containing motif 1 (SARM1), an adaptor molecule that we found to be directly involved in neuronal damage. SARM1-mediated cell death was associated with induced oxidative stress response and mitochondrial damage. These studies provide an innate-immune signaling mechanism for virus-induced neuronal death and reveal potential targets for development of therapeutics to treat encephalitic viral infections.